2019
DOI: 10.1177/1724600819876951
|View full text |Cite
|
Sign up to set email alerts
|

High expression of IQGAP3 indicates poor prognosis in colorectal cancer patients

Abstract: Background: The oncogene IQ motif-containing GTPase activating protein 3 (IQGAP3) is ubiquitously overexpressed in several human cancers. This study was designed to explore the expression and role of IQGAP3 in colorectal cancer. Methods: We first assessed the IQGAP3 expression level in colorectal cancer. The correlation of IQGAP3 expression with the clinicopathological characteristics and prognosis was then assessed. At last, we investigated the function of IQGAP3 in colorectal cancer by knocking down its expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…CRC is one of the most dangerous cancers and its global incidence and mortality have increased markedly over the past decades. Though genetic and epigenetic changes of CRC have been broadly reported, the molecular mechanisms in the development of CRC remain to be further explored [ 29 ]. We aim to investigate the role of CRCSC-derived exosomal miR-17-5p during CRC development with the involvement of SPOP.…”
Section: Discussionmentioning
confidence: 99%
“…CRC is one of the most dangerous cancers and its global incidence and mortality have increased markedly over the past decades. Though genetic and epigenetic changes of CRC have been broadly reported, the molecular mechanisms in the development of CRC remain to be further explored [ 29 ]. We aim to investigate the role of CRCSC-derived exosomal miR-17-5p during CRC development with the involvement of SPOP.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al found that IQGAP3 had high expression in breast cancer tissues and cell lines, and its high expression was correlated with the clinical stage, tumor node metastasis stage, and a poor prognosis ( Hua et al, 2020 ). High expression of IQGAP3 has been observed in colorectal cancer ( Wu et al, 2019 ), hepatocellular carcinoma ( Shi et al, 2017 ), bladder cancer ( Xu et al, 2019 ), and gastric cancer ( Huang et al, 2021 ). Hence, IQGAP3 appears to have important roles in cancer progression and could be a promising biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…IQGAP3 has also previously been implicated in the proliferation of epithelial cells (27). Moreover, previous studies have revealed the role of IQGAP3 in the proliferation and metastasis of lung, gastric, breast, pancreatic cancer, and colorectal cancer as well as hepatocellular carcinoma (29)(30)(31)(32)(33)(34)(35). Therefore, the role of IQGAP3 is crucial in the malignant transformation of several types of cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, IQGAP3 is hypothesized to be involved in the proliferation of epithelial cells (27), and is a novel member of the IQGAP family, which was discovered in 2007 (28). IQGAP3 is located on chromosome 1 at 1q21.3 loci and has been reported to act as an oncogene in several types of cancer (29)(30)(31)(32)(33)(34)(35). Furthermore, IQGAP3 is a transmembrane protein, and has been speculated to be a potential therapeutic target (35).…”
Section: Iqgap3 Promotes Cancer Proliferation and Metastasis In High-grade Serous Ovarian Cancermentioning
confidence: 99%